A power aware mechanism for energy efficient routing in MANET. (19th July 2019) - Sekar, P. Chandra; Mangalam, H.
In this paper, mobile ad hoc network (MANET) is used to refer a wireless network wherein there is no definite architecture and required configuration is done by itself. Multiple protocols are suggested to reduce the overall transmission power in MANET routing. Several multicasting routing protocols are available and two of them are power aware dual tree based multicast routing protocol (PDTMRP) and load balancing and power aware multicast routing in MANET (LPMR). Here, a power aware mechanism for energy efficient routing (PAMER) for MANET is designed to improve route stability as well as to obtain load balance data transmission by taking into account the energy reduction rate (ERR) as well as residual energy (RE). A suitable band width (BW) assessment is integrated to respond to network traffic as well as explore a QoS aware strategy into route discovery for appropriate traffic management. Thus, the improved system can monitor overhead, lessen the number of route reconstruction as well as improve the life span of network.